Differential RNAi efficacy of siRNA and dsRNA targeting key genes for pest control in Spodoptera litura - Lin, Yu-Chun; Lu, Yun-Heng; Liu, Yun; Su, Yu-Juan; Lin, Yu-Hsien; Wu, Yueh-Lung (Frontiers in Insect Science, 2025)
RNA interference (RNAi) is a promising gene-silencing technique for pest control that targets essential genes. We assessed the potential of double-stranded RNA (dsRNA) and small interfering RNA (siRNA) to silence mesh or iap genes in the midguts of Spodoptera litura larvae. Despite the theoretical promise of RNAi approaches, our findings revealed that dsRNA did not induce significant gene silencing or impact larval growth, whereas siRNA exhibited clear insecticidal effects, likely by disrupting intestinal osmoregulation and impairing larval fitness. Detailed analysis indicated that dsRNA could not be efficiently converted into functional siRNA in the midguts of S. litura, possibly due to the low expression levels of Dicer-2 and the rapid degradation of dsRNA within the gut environment. Furthermore, while dsRNA demonstrated greater environmental stability than siRNA under soil conditions, the inability of S. litura to process dsRNA effectively limits its viability as a pest control agent. These findings indicate the critical role of Dicer-2 in RNAi-mediated gene silencing and highlight the challenges and limitations of employing dsRNA-based genetic pesticides in lepidopteran species.